Technical drawings - Scales : - International Organization for Standardization
Indicates recommended scales and their designation for use in any field of engineering. Gives definitions for the scale types and relevant terms. The complete designation shall consists of the word "SCALE" (or its equivalent in the language used in the drawing) followed by the indication of its ratio.